Performance Evaluation Of Enhanced Velocity-Based Handoff Algorithm For Vanet - Emami, Arsalan; Jalooli, Ali; Michael, Oche; Md Noor, Rafidah; Ahmedy, Ismail; Salleh, Rosli (Malaysian Journal of Computer Science, 2014)
Vehicular Ad Hoc Networks (VANETs) is based on 802.11p standard where a vehicle is connected to a base station in a dynamic manner. The vehicle is traversed from one base station to another and may affect the transmission of packets. To minimize the disruption, handoff latency must be kept at minimum duration. This paper presents an improvement of existing handoff mechanism based on vehicle’s velocity. The proposed algorithm is called Enhanced Velocity Handoff (EVHO) where it is defined based on two rules ofa mobility model; vehicle speeds and handoff latency. Each rule provides different equations and transforms them into the EVHO algorithm. EVHO algorithm created a new packet frame for neighboring vehicles for transmission. The experiment of EVHO is conducted using a network simulator, NS-2. The results are compared with existing velocity-based handoff and some significant improvements on packet delay, packet loss rate and network throughput are shown.